Uma obra do matemático jesuíta Manuel de Campos para a "Aula da esfera" do Colégio Santo Antão - Loreto Junior, Armando Pereira (2001)
This research investigates which were the mathematical contents, sequence and manner of exposition taught in the sphere class of Colégio de Santo Antão-OVelho, in Lisbon, during the second half of the 18th century. The current work describes, within the context of that time, the most relevant features of the compendium Trigonometria Plana e Esferica com o Canon Trigonometrico, Linear e Logarithmico, published in 1737. Its author is the Jesuit priest Manoel de Campos, who was one of the teachers of that class. This study reveals interesting approaches made by him, which led to important results, like the correction of the Canon Trigonometrico, and the generation of the logarithmic curve. It was verified that the trigonometry presented by Campos had as its first objective the application to the Nautical Science and Astronomy. However, the author did not present these applications in his book, but promised to show them in another publication, which existence we did not find register of. Because of that, some examples of those applications, included in Arte de Navegar of Manoel Pimentel, were selected and presented in this work